DIALOG PAI DAN FILSAFAT PENDIDIKAN BARAT(Al-Ghazali, Ibnu Khaldun, Dewey, Freire, Habermas) - Harmina; Syaifuddin Sabda; Husnul Yaqin; Hamdan (Advances In Education Journal, 2025)
Education is a fundamental pillar in shaping intellectually, morally, and spiritually balanced individuals. This study addresses the differences and similarities in the concepts and objectives of education from Islamic and Western perspectives amid the challenges of globalization and technological advancement. This research aims to analyze the concepts, goals, and characteristics of education according to Islamic and Western philosophers. This study employs a qualitative approach using library research by examining relevant books, journals, and scholarly publications. The findings show that Islamic education emphasizes the integration of faith, morality, and knowledge, while Western education focuses on rationality, empiricism, critical thinking, and practical skills. This study highlights the importance of integrating moral and spiritual values into the modern education system. In conclusion, Islamic and Western educational perspectives can complement each other in forming balanced individuals intellectually, ethically, and socially.